Innovative Approaches to ESP in Advertising: Technology, Visual Literacy, and Curriculum Evolution - Acfira, Lukytta Gusti (Universitas Terbuka, 2024)
This study delves into integrating technology, visual literacy, and curriculum development within English for Specific Purposes (ESP) in advertising education. By exploring innovative approaches to ESP instruction, the research aims to address the evolving needs of learners and the advertising industry. Through a comprehensive literature review and analysis of previous research, the study seeks to evaluate the effectiveness of integrating technology and visual literacy into ESP advertising curriculum. This study used a descriptive approach, which systematically identified and selected relevant literature from academic databases, scholarly journals, books, and other reputable sources. Keywords related to each area of focus were used to conduct comprehensive searches. Inclusion and exclusion criteria were established to ensure the selected literature aligns with the research objectives. Findings indicated that the integration of technology and visual literacy into ESP advertising curriculum enhances learner engagement, creativity, and proficiency in creating advertising materials. Additionally, curriculum development strategies such as needs analysis, stakeholder collaboration, and continuous evaluation contribute to the relevance and effectiveness of ESP instruction. The findings of this study have significant implications for ESP educators, curriculum developers, and advertising professionals. By integrating technology, visual literacy, and curriculum development strategies into ESP advertising education, educators can better prepare learners for success in the dynamic and competitive advertising industry. Furthermore, the study underscores the importance of ongoing collaboration between academia and industry to ensure the continued relevance and effectiveness of ESP instruction in meeting the evolving needs of learners and the advertising industry.